The Effect of Character and Local Wisdom-Integrated Causalitic Model Learning on Problem-Solving Skills and the Development of Environmental Conservation Literacy - Arum, Bq Puspita; Rokhmat, Joni; Zuhdi, Muhammad; Sutrio, Sutrio (Department of Physics Education, Universitas Mataram, 2023)
The study aims to examine the effect of a causalitic learning model that integrates character and local wisdom on problem solving ability (PSA) physics and environmental conservation literacy (ECL) development of students. The type of research used was quasi-experimental with an untreated control group design with pretest-and posttest. The population is all class X students of SMAN 1 Terara, totaling 206 people. The research sample was taken using purposive sampling technique so that 31 students from X MIPA 6 class were selected as the experimental group and 31 students from X MIPA 3 class as the control group. The experimental group was treated in the form of a causalitic learning model integrated with character and local wisdom, while the control group was treated in the form of a conventional learning model. The PSA instrument consists of tests in the form of descriptive questions taking into account validity, reliability, level of difficulty of the questions, as well as the differential power of the questions and ECL development tests in the form of questionnaires. The average PSA value obtained in the experimental group was 79,87 and in the control group was 72,39. The average score for the development of ECL in the experimental group was 80,00 and that of the control group was 42,58. The data of both classes are homogeneous and normally distributed. Data on PSA and development of ECL were analyzed using t-test polled variance with a significant level of 5%. The results of the PSA analysis were obtained at 4,32 and the results of the ECL development analysis were obtained at 10,94. Thus, it can be concluded that there is an influence of the integrated causalitic learning model of character and local wisdom on PSA and the development of ECL.